A COMPARATIVE ANALYSIS OF MINIMAL PAIRS IN HAUSA AND ENGLISH LANGUAGES - Ibrahim Ahmad, Shehu; Monica Alaku , Emmanuel; Salamatu Kwoku , Suleiman (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
The paper aimed at doing a comparative analysis of minimal pairs in Hausa and English Languages with a view to bring to bare the problems Hausa speakers of English have in pronouncing English minimal pairs by means of comparison. The study is motivated into this investigation by some observed speech features of some Hausa speakers of English as they communicate in English. This is observable when, for instance, a typical Hausa native seems to give some English minimal pairs similar pronunciations irrespective of the sound contrast distinguishing them. Thus, one hears a Hausa speaker of English pronouncing the following pairs of words: cope, cop and cup; fame and firm; pen and pain; mother and murder; fun and phone; foam and form etc as if they were the same in spelling, pronunciation and meaning. It established the basic factor affecting the Hausa pronunciation of English minimal pairs. Contrastive Analysis Hypothesis developed by Robert Lado (1957) and Classical Phonology were used as theories for analysis. Data were collected through audio-tape recording. A Sensonic (Sony Recorder) was used as an instrument in recording. The population is drawn from three states in Northern Nigeria. The analysis revealed that most English and Hausa minimal pairs initial and final are consonantal, while medial are vowel based. Tone played a prominent role in distinguishing two or more lexical items in Hausa language. It recommended that the Hausa speakers of English (especially those in the study area) should make stringent effort to become fully aware of their innate tendencies to commit the pronunciation errors identified in this research work, so that they will be able to identify areas of similarity as well as difference between English and Hausa.